PENGARUH INTERNASIONALISASI TERHADAP NILAI PERUSAHAAN PADA SEKTOR FMCG DI INDONESIA - Alvyola Permata Yussanto; Helianti Utami; Makaryanawati (Merwin Publisher, 2026)
This study aims to examine the effect of internationalization on firm value in the Fast Moving Consumer Goods (FMCG) sector in Indonesia. Amid stagnant domestic demand and increasing economic uncertainty, internationalization is often perceived as an alternative strategy to enhance firm value through market expansion and risk diversification. However, prior empirical studies report mixed findings, particularly in the context of emerging markets. This study employs a quantitative approach using panel data consisting of 173 firm-year observations of FMCG firms listed on the Indonesia Stock Exchange. Firm value is measured using Tobin’s Q, while internationalization is proxied by the ratio of foreign sales to total sales. Panel regression analysis is applied after all models satisfy classical assumption tests. The results indicate that internationalization has a negative and significant effect on firm value. This finding suggests that international expansion has not been perceived as a value-creating strategy by investors and is instead viewed as an additional source of risk. From a Resource-Based View perspective, the results imply that internationalization has not yet been transformed into a valuable strategic resource due to limitations in internal capabilities and organizational readiness. This study contributes to the internationalization literature by providing evidence from the FMCG sector in an emerging market context and emphasizing the importance of internal resource preparedness in achieving firm value creation.